An Analysis of Research Contributions of Tumkur University Based on JGate Plus (JCCC) - Raviivvenkat, B.; Subash Reddy, B. (Journal of Information and Knowledge, 2019)
This study evaluates the research output of Tumkur University using J-Gate Custom Content for Consortium (JCCC). The research papers indexed in JGate Plus were considered for the analysis. Some scientometric indicators have been examined to have a better understanding of the growth and current status of the research output of the University.